Agronomic aspects of two Physalis species as a function of Nitrogen fertilization - Bertoncelli, Douglas Junior; Oliveira, Marisa de Cacia; dos Passos, Amanda izabel; Casagrande, Taylon Henrique; Ariati, Ana Claudia (Comunicata Scientiae, 2018)
The cultivation of small fruits has been increasing with good economic returns, and among these, the genus Physalis has been an important alternative source of income due to the high value and possibility of cultivation in small areas. However, there is not established fertilization for this crop and considering that nitrogen is one of the most limiting nutrients for the growth and development of plants, this study aimed to evaluate the agronomic aspects of two species of Physalis submitted to different N doses. The experiment was conducted in a greenhouse in a completely randomized design, using two species (Physalis pubescens and P. peruviana) and five N doses (0, 200, 250, 300 and 350 kg ha-1), and seven replications. The plant height, dry mass of aerial part and roots, the number of branches, root length, yield and average fruit mass were evaluated. In these experimental conditions, it was observed that for P. peruviana the dose of 250 kg ha-1 N resulted in a greater yield of fruit per plant, as for P. pubescens the dose of 350 kg ha-1 N showed a more efficient performance.